2015
DOI: 10.1007/s13197-015-2145-0
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extraction parameters on physico-chemical characters and antioxidant activity of water soluble polysaccharides from Macrocybe gigantea (Massee) Pegler & Lodge

Abstract: Polysaccharides from mushrooms are potentially active pharmaceutical ingredients and their action is dependent upon conformation, composition, size etc. In this context, three water soluble crude polysaccharide rich fractions viz. hot water extracted polysaccharide (HWP), cold alkaline extracted polysaccharide (CAP) and hot alkaline extracted polysaccharide (HAP) have been isolated using varying extraction parameters from Macrocybe gigantea, a well-known edible mushroom collected from Gangetic plain of West Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
(39 reference statements)
3
24
0
Order By: Relevance
“…Firstly, chemical parameters of MLHWP were analysed spectroscopically which can be ranked in the following order: carbohydrates > protein (Table ). Carbohydrates, especially β‐glucan constituted the major proportion of this crude polysaccharide and its relative composition of is very much allied with previous published research findings on Russula alatoreticula , Macrocybe gigantea , Lentinus squarrosulus , Ganoderma applanatum and others.…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…Firstly, chemical parameters of MLHWP were analysed spectroscopically which can be ranked in the following order: carbohydrates > protein (Table ). Carbohydrates, especially β‐glucan constituted the major proportion of this crude polysaccharide and its relative composition of is very much allied with previous published research findings on Russula alatoreticula , Macrocybe gigantea , Lentinus squarrosulus , Ganoderma applanatum and others.…”
Section: Resultssupporting
confidence: 69%
“…The band at 883.6 cm À1 confined that the polysaccharide possessed b glycosidic linkages between sugar residues. [26] Altogether, the spectrum demonstrated that MLHWP was a b-glucan with pyranose sugar residues linked through b glycosidic bonds although little amount of phenols and proteins were co-extracted with polysaccharide.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…The giant sized macrofungi Macrocybe gigantea (Massee) Pegler & Lodge 6 was collected from Agumbe rainforest. More fruiting bodies of M. gigantea are found during continuous rain with an average relative humidity of 70% and temperature range between 25 -28 º C. M. gigantea is a common edible mushroom which grows in regions of high temperature and humidity and distributes in subtropical rain forests in Africa and Asia 7. In India, this macrofungus has been documented from three states, viz., Kerala, Karnataka and West Bengal 8,9,10 . This Basidiomycetes fungus belongs to the family Catathelasmataceae.…”
Section: Introductionmentioning
confidence: 99%